Psychosomatic Effects of Sexual Harassment and Violence on Undergraduate University Female Students; A Cross Sectional Prevalence Study - Makloph MG (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Sexual harassment is the plague of that century due to its tremendous prevalence in varioussocieties ,it is unwanted and unaccepted sexual conduct with a female either verbal, non verbal or physical,and it affects the physical and psychological wellbeing of the victim..Patients and Methods : Cross- sectional study was done during the period of october 2019 till January2020. five hundred and four participant aged between 19 and 25 years old randomly selected , distributedon nine faculties , a questionnaire constructed of three parts given to each participant to collect data abouttype of abuse and psychosomatic effect through the use of standardized questionnaire The collected datawere organized, tabulated, and statistically analyzed using statistical package for social science (SPSS Inc,version 18).Results: The study showed significant relationship between physical harassment and psychosomatic effectsalso method of harassment and frequency of harassment is a risk factor for occurrence of psychosomaticeffects, and family response regarding perpetrator affect profoundly psychosomatic effects. the main harasserwere university students.Conclusion: The prevalence of sexual harassment now days resemble a cancer due to its wide spread anddiffusion within the societies and its profound effect on the well being of the victim causing profoundpsychosomatic effects . these effects are affected by the method of harassment and the frequency of exposure.Families should have strong reflex against the perpetrator as this help the victim recovery and affects itsprofound effects on her well being.